The role of learner-learner interaction in the development of speaking skills - Saeed, Karwan Mustafa; Khaksari, Mahta; Eng, Lin Siew; Abdul Ghani, Ahmad Mahreez (ACADEMY PUBLICATION, 2016)
The present study investigated the role of learner-learner interaction in the development of speaking skills of 52 international postgraduate students who enrolled in an intensive English course at the language center at Universiti Utara Malaysia (UUM) after they failed in English Language Placement Test (ELPT) at the point of entry to the university. A quantitative research method was employed to examine the role of learner-learner interaction in the development of speaking skill of the language learners.The speaking skill of the participants was assessed before and immediately after the English course and, questionnaire was distributed among the participants to get a deeper insight about the role of learner-learner interaction in enhancing their speaking skill.The data gained were analysed through SPSS version 16.0 and were presented in the form of descriptive statistics which include percentages.Findings of the study indicated that learner-learner interaction played a significant role in the classroom since students were able to improve their speaking skill in the classroom atmosphere.The analysis also confirmed notable concern over employing learner-learner interaction instructions in the developing of speaking skill. The pedagogical implications of the findings suggested the need to include communicative language teaching materials which help language learners practice language in the hope of improving their speaking abilities through the interactions that take place among language learners in the classroom.